Integrated planar and bulk dual heterojunctions capable of efficient electron and hole extraction for perovskite solar cells with >17% efficiency. (February 2017) - Wu, Wu-Qiang; Chen, Dehong; Li, Feng; Pascoe, Alexander R.; Cheng, Yi-Bing; Caruso, Rachel A.
Abstract: To achieve high-performing perovskite solar cells (PSCs) interfacial engineering of the perovskite thin film and charge carrier-selective layers is vital for fast extraction of photogenerated electrons and holes, and the suppression of electron-hole recombination. Herein, a glucose-assisted self-assembly solvothermal protocol is reported to prepare electron-rich TiO2 thin films as effective electron transport layers exhibiting enhanced electron mobility. Bilayer structured CH3 NH3 PbI3 perovskite films are spontaneously formed, consisting of a flat and dense bottom layer forming the TiO2 /CH3 NH3 PbI3 planar heterojunction and a textured and porous top layer elongating in the vertical direction forming the CH3 NH3 PbI3 /spiroMeOTAD bulk heterojunction. The integrated planar and bulk dual heterojunction based PSCs are efficient in light harvesting and charge collection, and thus yield power conversion efficiencies up to 17.75% and a stabilized power output above 17.20%. Integrating both planar and bulk heterojunctions into a PSC assembly provides an effective approach for fabricating highly efficient perovskite optoelectronic devices. Graphical abstract: Highlights: Electron-rich TiO2 films are prepared via a glucose-assisted solvothermal process. Bilayer dense/porous CH3 NH3 PbI3 films are formed. Efficient light harvesting and charge collection within devices realized. Integrated planar/bulk heterojunction solar cell attains an efficiency of 17.75%.